Adoption and intensity of integrated agriculture aquaculture among smallholder fish farmers in Kenya - Awuor, Fonda Jane; Macharia, Ibrahim Ndegwa; Mulwa, Richard Mbithi (Frontiers in Sustainable Food Systems, 2023)
This paper examined the adoption and intensity of using integrated agriculture aquaculture (IAA) among smallholder fish farming households in Kenya. The analysis was based on crossectional farm-level data collected from four counties in Kenya: Nyeri, Kakamega, Siaya, and Busia. Results showed that risk plays a central role in farmers’ decisions through the direct effect of the sample moments of the profit distribution. Specifically, the first moment (mean profit) had a highly significant positive effect on the adoption and intensity of IAA. Profit variability, as reflected by the second moment, negatively impacted adoption and the intensity of IAA. Other factors that were important in IAA adoption included the proportion of economically active members, full-time land ownership, awareness of IAA, accessibility to irrigation, and flat farm topography, all of which were statistically significant in influencing IAA adoption positively. Other factors which were found to influence the intensity of IAA positively and significantly were: age, education level, number of economically active members, full-time land ownership, awareness of IAA, flat farm topography, and clay soil type. Thus, IAA should be promoted alongside farmers’ education, farm size, access to affordable and accessible credit, number of farm enterprises, and IAA awareness as a mechanism for enhancing smallholder IAA adoption and intensity of use.